LEGAL CULTURE DECONSTRUCTION IN INDONESIAN LEGAL SYSTEM - Sulaksono (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Along with the reformation development in Indonesia, the new demand was created and realized with the implementation of law in society. The implementation of laws and regulations is a critical component of law enforcement. It entails legal officers' and society's willingness to enforce the law in order to maintain social order and establish justice. This research is normative juridical research that provides a qualitative analysis of discussed material by analyzing theories, legal principles, and law. From the research result, it found that the law and regulation in Indonesia is still weak and need to be improved. With the implementation of law and regulations in Indonesia, there are many obstacles and problems faced in its enforcement. As an example, the court justice is still doubt in issuing the law or regulations for the government or any political parties. Legal system consists of three components: legal structure, legal substance, and legal culture. These three elements are interconnected and have positive implications for the development of a responsive legal system. According to the research findings, the Indonesian legal system is repressive because the three elements of the legal system demonstrate its equality.